Towards the development of a protocol for cryopreservation of petai (parkia speciosa hassk.) zygotic embryos. - Lim, S.P.; R.S., Uma (2001)
This study was carried out to evaluate the potential of cryopreservation technique for germplasm conservation of petai zygotic embryos. The effect of various desiccation periods and different concentration of sucrose pretreatment on survival of petai embryos in liquid nitrogen (LN) was evaluated. The result shows that non-pretreated petal embryos were sensitive to desiccation whereby a reduction of moisture content to below 16% decreased survival percentage to less than 48%. On freezing, no embryos survived irrespective of their moisture content. Sucrose pretreatment was found to enhance desiccation and freezing tolerance in petai embryos whereby survival percentage of approximotely 90"/6 and 50% was observed, without and with LN exposure respectively.